2022
DOI: 10.3991/ijet.v17i03.27151
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Digital Literacy Based on Students’ Interest in Digital Technology, Internet Costs, Gender, and Learning Outcomes

Abstract: This study aims to analyze students' digital literacy in the context of learning biology material on the digestive system and identify students' digital literacy in terms of interest in digital technology, internet costs, gender, and learning outcomes. The research was conducted at one private high school in Medan, Indonesia. The instrument used is a questionnaire and a list of student grades from the teacher. The results showed that students interested in digital technology had a significantly higher digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…(Yu, 2022) Likewise, a keen interest in digital technology tends to increase digital literacy. (Brata et al, 2022) Therefore, digital literacy functions to protect the younger generation by increasing education, preferences and interest in understanding digital technology.…”
Section: Literature Studymentioning
confidence: 99%
“…(Yu, 2022) Likewise, a keen interest in digital technology tends to increase digital literacy. (Brata et al, 2022) Therefore, digital literacy functions to protect the younger generation by increasing education, preferences and interest in understanding digital technology.…”
Section: Literature Studymentioning
confidence: 99%
“…The influence of digital literacy on learning achievement is 19.4%. Another research reported that students interested in digital technology had a significantly higher digital literacy score than students who had less interest in digital technology (Brata et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It is related to reading, writing, calculation skills, and effective use of technology in personal, social, and professional areas. It is also considered inseparable from the social and educational needs of the society in which we live (Larraz, 2013 ; Brata et al, 2022 ). Therefore, we refer to a concept that has several aspects including the technological aspect, the informative and multimedia aspect, and the communicative aspect.…”
Section: Introductionmentioning
confidence: 99%